How Cellular Agriculture Systems Can Promote Food Security - Soice, Emily; Johnston, Jeremiah (Frontiers in Sustainable Food Systems, 2021)
Cellular agriculture, the manufacturing of animal-sourced foods by cell cultures, may promote food security by providing a food source that is available, accessible, utilized, and stable. The extent to which cellular agriculture can promote food security, however, will depend in part on the supply system by which it produces food. Many cellular agriculture companies appear poised to follow a centralized supply system, in which production is concentrated within a small number of large plants and products are distributed over a wide area. This model benefits from economies of scale, but has several weaknesses to food security. By being built of a handful of plants with products distributed by a large transportation network, the centralized model is vulnerable to closures, as became clear for animal-sourced centralized system during the COVID-19 pandemic. Cellular agriculture systems are being built now; therefore, alternative supply system models of decentralized and distributed systems should be considered as the systems of cellular agriculture production are established. This paper defines both the requirements of food security and three possible supply system models that cellular agriculture could take and evaluates each model based on the requirements of food security.